EXPERIMENTAL INFECTIONS OF MILKY HEMOLYMPH DISEASE IN SPINY LOBSTER Panulirus homarus - Sudewi Sudewi; Zeny Widiastuti; Bejo Slamet; Ketut Mahardika (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2018)
Milky hemolymph disease of spiny lobster (MHD-SL) is categorized as the most destructive disease in farming spiny lobster. Therefore, it is required to investigate the routes of milky disease infection in spiny lobster as a basic knowledge in order to prevent milky disease transmission. The aim of the present study was to perform an experimental infection of milky disease in spiny lobster Panulirus homarus. Experimental infection of milky disease was carried out by several modes of infection which were injection, immersion and per os exposure. Injection of each 0.2 mL undiluted and diluted hemolymph from the diseased lobster resulted in a cumulative mortality of 100% at 15 days post-infection (dpi), and 75% at 16 dpi, respectively. Experimental infection through water immersion caused in a cumulative mortality of 50% at 7 dpi. In contrast, no mortality was observed in per os exposure as well as in control groups. Results of this experimental study provided evidence for horizontal transmission of MHD-SL among P. homarus. Histopathological analysis exhibited that there were masses of Rickettsia-like bacteria (RLB) in the connective tissues of the gill, hepatopancreas, gonad, midgut, and muscle tissues of the affected lobsters. Mass of RLB was not only found in the moribund lobsters but also in the surviving lobsters with milky hemolymph appearance.